Alprazolam therapy effects on quality of life and vegetative dysfunction syndrome in patients with idiopathic mitral valve prolapse - E. V. Akatova; E. D. Sukhanova; O. P. Nikolin; A. I. Martynov (Кардиоваскулярная терапия и профилактика)
Aim. To assess quality of life (QoL) and severity of vegetative dysfunction syndrome (VDS) in patients with idiopathic mitral valve prolapse (MVP); to evaluate the effects of alprazolam therapy on QoL and VDS. Material and methods. This single-blind, placebo-controlled study included 60 patients with idiopathic MVP (33,3% men, 66,7% women). All patients were randomised into two groups: the main group (MG), receiving alprazolam, and the control group (CG), receiving placebo. Both groups were comparable by age (mean age 30,8±0,4 and 31,1±0,2 years, respectively) and gender structure. In all patients with idiopathic MVP, organic internal pathology was ruled out. Both groups underwent complex examination at baseline and 10 weeks after the therapy started. Results. Clinically significant effectiveness of the treatment (VDS severity reduction (in points) by at least 50%, comparing to the baseline level) was observed among 80,0% of the patients receiving alprazolam (71,4% men, 82,6% women) and only in 33,3% (58,3% men, 16,7% women) of the controls. Alprazolam was clinically effective by the “DISS-work” scale in 30% (28,6% men, 30,4% women), by the “social life” scale – in 43,3% (57,1% men, 39,1% women), and by the “personal relationships” scale – in 56,7% (42,8% men, 60,9% women). In the placebo group, the respective percentages were 43,3% (50% men, 38,9% women), 30,0% (41,7% men, 22,2% women), and 46,7% (58,3% men, 38,9% women). Conclusion. Alprazolam therapy demonstrated significant QoL improvement and VDS severity reduction in patients with MVP.